2015 IEEE Nuclear Science Symposium and Medical Imaging Conference (NSS/MIC) 2015
DOI: 10.1109/nssmic.2015.7582218
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing highly accurate relative stopping powers in proton computed tomography

Abstract: Proton computed tomography (pCT) is an evolving tomographic imaging modality with applications in proton and ion therapy. The method allows direct reconstruction of relative stopping power of patient tissues in a 3D-fashion. The pCT collaboration has built first experimental prototypes of pCT scanning systems [1] and has developed approaches to reconstruct proton CT images based on registering the coordinates and water equivalent path length (WEPL) of individual protons traversing the scanned volume. From thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Another benefit of NTVS is that it allows feasibility-seeking to be performed with a larger relaxation parameter λ than was appropriate with OTVS (λ = 0.0001, k = 12). It was found that with NTVS, the same RSP error can be obtained with λ = 0.0002 after performing k = 6 feasibility-seeking iterations without producing larger standard deviations, as previously experienced in practice with OTVS, which lead to the choice of λ = 0.0001 in previously published work with the simulated data set [42], [36]. Arriving at an acceptable solution in k = 6 feasibility-seeking iterations also offers substantial computational benefit.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Another benefit of NTVS is that it allows feasibility-seeking to be performed with a larger relaxation parameter λ than was appropriate with OTVS (λ = 0.0001, k = 12). It was found that with NTVS, the same RSP error can be obtained with λ = 0.0002 after performing k = 6 feasibility-seeking iterations without producing larger standard deviations, as previously experienced in practice with OTVS, which lead to the choice of λ = 0.0001 in previously published work with the simulated data set [42], [36]. Arriving at an acceptable solution in k = 6 feasibility-seeking iterations also offers substantial computational benefit.…”
Section: Discussionsupporting
confidence: 51%
“…Details of the pCT data preprocessing, calibration, and image reconstruction have been presented previously [36], [37]. For the purposes of this work, feasibility-seeking was performed using the DROP algorithm of [38] with blocks containing 3200 (simulated data set) and 25,600 (experimental data set) proton histories.…”
Section: Data Preprocessing and Implementation Details Of Image Rementioning
confidence: 99%
See 1 more Smart Citation
“…It is a challenge to complete the image reconstruction in a time interval comparable to the sixminute data acquisition, but Ordoñez demonstrated that it can be accomplished in only 4.5 minutes using ten compute nodes, each with twelve cores and two GPUs. Similarly, using different code Schultze demonstrated (Schultze, 2015) that a similar image could be reconstructed in 6.5 min on a single Xeon compute node using one NVIDIA K40 GPU. Figure 4 shows a reconstructed image of a CTP404 Geometry and Sensitometry module called the "sensitometry" phantom, a plastic cylinder with an assortment of cylindrical inserts (Catphan TM 504 phantom by The Phantom Laboratory, Salem, NY).…”
Section: Image Reconstruction and Scanner Performancementioning
confidence: 99%
“…Various concepts ranging from advanced detector designs to appropriately selecting the preprocessing techniques and parameters of the reconstruction algorithm have a major impact on the quality and accuracy of the pCT images [4], [5]. Calculating accurate RSPs is of great importance, but to take advantage of the pCT systems in a clinical setup, there is also a great need for real-time algorithms that can process hundreds of millions of protons in concise time frames not more than a few minutes.…”
Section: Introductionmentioning
confidence: 99%